Spatiotemporal changes in diffusion, T2 and susceptibility of white matter following mild traumatic brain injury. (5th May 2016) - Li, Wei; Long, Justin Alexander; Watts, Lora; Shen, Qiang; Liu, Yichu; Jiang, Zhao; Duong, Timothy Q.
Abstract : Impaired white matter integrity in traumatic brain injury (TBI) can lead to deficits in various neurological functions. The differentiation of the underlying pathological processes, e.g. edema, demyelination, axonal damage, to name a few, is of key clinical interest for the assessment of white matter injury. In this study, a combination of T 2, diffusion and susceptibility MRI was used to study the spatiotemporal changes in white matter at 1 h, 3 h, and 1, 2, 7 and 14 days following TBI, using a rat controlled cortical impact (CCI) model. Based on radial diffusivity (RD), the rats were divided into two groups: group 1 showed widespread increases in RD along the corpus callosum of the ipsilesional hemisphere at day 2, and group 2 showed normal RD. Based on this group separation, group 1 also showed similar widespread changes in fractional anisotropy (FA) and T 2 at day 2, and group 2 showed normal FA and T 2 . The widespread changes in RD and T 2 in group 1 on day 2 were apparently dominated by edema, which obscured possible myelin and axonal damage. In contrast, the susceptibility of group 1 showed more localized increases near the impact site on day 2, and otherwise similar contrast to the contralesional hemisphere. The localized susceptibility increase is probably a result of demyelination and axonal injury. The extent of brain damage between the two groups revealed by MRI was consistent with behavioral results, with the first group showing significantly increased forelimb asymmetry and increased forelimb foot fault deficits. Our results suggest that the combination of T 2, diffusion and susceptibility MRI may provide an opportunity for the differential assessment of edema and axonal damage in TBI. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : T 2 diffusion and susceptibility MRI were used to study the spatiotemporal changes in white matter following traumatic brain injury, using a rat controlled cortical impact model. Two groups of animals were differentiated: group 1 showed widespread changes in T 2 and diffusion in the ipsilesional hemisphere at day 2, and group 2 showed no changes. The widespread changes in T 2 and diffusion in group 1 were dominated by edema. The localized susceptibility increase was probably caused by myelin and axonal damage.